Examining the Effects of Kiai Leadership, Institutional Support, and Educational Technology on Student Satisfaction in Indone-sian Pesantren - Sofwan Manaf; Ade Sofyan Mulazid; Hadiyanto Arief; Much Hasan Darojat; Duna Izfanna; Miftah Hur Rahman Zh; Musthofa Musthofa (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2026)
Indonesian pesantren faces a dual mandate: preserving spiritual and moral foundations while adapting to digital-age expectations. However, empirical evidence on which institutional drivers shape student satisfaction in this hybrid setting remains thin. This study examines the direct effects of Kiai leadership, institutional support, educational technology, and student involvement on student satisfaction across Indonesian pesantren. A quantitative cross-sectional design involving 480 stakeholders (active students, educators, alums, and institutional management) was used. Data were collected via a closed-ended Likert-scale questionnaire adapted from validated instruments and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) on SmartPLS 3.0, with bootstrapping (5,000 resamples), f² effect size, Q² predictive relevance, and inner VIF assessment. Results show that Kiai leadership (β = 0.420, p < 0.05) and institutional support (β = 0.374, p < 0.05) are the strongest predictors of student satisfaction. Educational technology exerts a smaller yet significant positive effect (β = 0.253, p < 0.05). Student involvement, contrary to the engagement-satisfaction canon, shows no significant direct effect (β = -0.541, p > 0.05), suggesting its meaning in pesantren departs from Western engagement constructs. The findings reposition spiritual-transformational leadership and ethically framed institutional support as the foundational determinants of satisfaction in faith-based education, with technology functioning as an enabler rather than a primary driver. Practical implications underscore the need to invest in Kiai leadership development and student-centred support systems, while future research is invited to develop culturally grounded engagement scales for pesantren contexts.